Influence of split application of potassium on growth, yield and potassium dynamics under rice establishment methods - Sharanagouda Yamanappagouda; Ananthakumar, M. A; Denesh, G. R.; Prakash, S. S.; Shivakumar, K. V. (Annals of Agricultural Research, 2023)
A field experiment was conducted during Kharif 2021 at ZARS, V.C. Farm, Mandya to study the influence of split application of potassium on rice under different establishment methods viz., dry direct seeded rice (DDSR), wet direct seeded rice (WDSR), system of rice intensification (SRI), alternate wetting and drying (AWD) in comparison to conventional method of transplanting as standard check. The experiment was laid out in factorial randomized complete block design and replicated thrice. Among the different rice establishment methods, system of rice intensification (SRI) recorded significantly higher growth and yield parameters viz., higher plant height (137.7 cm), number of tillers (583.0 m-2) and dry matter production (81.2 g hill1 ), higher number of panicles (359.4 m-2), grains per panicle (270.5), filled grains per panicle (233.5), grain yield (6412 kg ha-1) and straw yield (7483 kg ha-1) as compared to other methods. The growth and yield attributes differed non-significantly by split application of potassium and the interaction among the treatments. However, numerically three split application of potassium recorded higher values as compared to two split applications.The wet DSR recorded significantly higher content of available N, P2 O5 and K2 O (178.7, 39.3 and 160.6 kg ha-1, respectively) as compared to other methods of establishment. The lower N, P2 O5 and K2 O (140.0, 26.5 and 147.2 kg ha-1, respectively) and potassium forms in the soil was recorded in SRI with three split application of potassium.The higher benefit cost ratio (B:C) (2.40) was recorded with three split applications of potassium in SRI method and hence considered as best establishment method with timely supply of potassium for achieving higher yield and net returns.